Direct Thermal Desorption (DTD) Extraction for Different Qualities of Agarwood Incense Analysis - Nurlaila, Ismail; Mohd Hezri Fazalul, Rahiman; Mohd Nasir, Taib; Mastura, Ibrahim; Seema, Zareen; Saiful Nizam, Tajuddin (IEEE, 2016)
Agarwood is well known as one of expensive and valuable woods due to its high demand in the market. As part of ongoing research in establishing agarwood oil quality grading, this paper presents Direct Thermal Desorption (DTD) in extracting commercial, high and low quality of agarwood incense. The Gas Chromatography - Flame Ionization Detection (GC-FID) and Gas Chromatography - Mass Spectroscopy (GC-MS) then are followed to analyze the compounds. All the identified compounds are tabulated and plotted. The result showed that high quality sample yielded the highest number of compounds, 35, followed by commercial, 32 and low quality sample, 9. It revealed that the highest relative peak areas (%) for compounds in three types of sample are different to each other. They are 8.98% (γ-gurjunene) in high quality, 11.95% (agarospirol) in low quality and 17.97% (hexadecanol) in commercial. Nine compounds, α-guaiene, β-selinene, agarospirol, guaia-1(10),11-dien-15-al, pentadecanoic acid, hexadecanol, eudesmol, guaia-1(10),11-dien-15,2-olide and 2-(2-phenylethyl) chromone exist in all samples but varied in their relative peak area (%). The finding using proposed method, DTD is significant, hence it will benefit further analysis especially for agarwood grading.